The town mouse and the country mouse - Ward, Helen, 1962-; Aesop (Somerville, Mass. : Templar Books, 2012)
A town mouse and a country mouse exchange visits and discover each is suited to his own home.
Kirkus Starred
Publisher's Weekly
School Library Journal starred
Kirkus Starred, August 2012
Publisher's Weekly, July 2012
School Library Journal starred, August 2012
Keywords: Fables; Folklore; Fables; Folklore; Fables; Folklore; Fables; Folklore; Picture books for children